See How They Run - McRobbie, David (Australia Puffin Books, 1996)
Emma's family is on the run, with nowhere to hide, no friend to share their secret, no past they can speak of. And if they're not watchful, they'll have no future. See how they run.
Keywords: Witnesses--Protection -- Teenagers -- Australia